The Role Of The National Sharia Council Fatwa In The Development Of The Sharia Financial Industry In Indonesia - Amanda Pramudita; Silvani Febrian; Muhammad Nur Iqbal (SEAN Institute, 2025)
Study This aiming For analyze the role of the National Sharia Council (DSN) fatwa in development industry Islamic finance in Indonesia. With use approach descriptive-qualitative , research This to study DSN's contribution in aspect regulation , supervision and innovation product Islamic finance . Data obtained through studies bibliography that includes study regarding the DSN fatwa, literature academic , and regulatory government related Islamic finance . Research results show that the DSN fatwa plays a role strategic in give runway laws and guidelines operational for institution Islamic finance , so that support sustainability and legitimacy industry This . The DSN fatwa also encourages innovation product Sharia compliant finance with need society and sharia principles . Although Thus , the challenge like difference fatwa interpretation and limitations literacy public Still need attention more carry on For increase effectiveness implementation of the DSN fatwa in Indonesia .